Penentuan Kadar Flavonoid Total Dan Uji Antioksidan Ekstrak Dan Fraksi N-Heksana-Etil Asetat-Air Kulit Delima Putih (Punica Granatum L.) Menggunakan Metode FRAP - Eny Wijayanti (Jurnal Medika Nusantara, 2023)
In the body there are a lot of free radicals that are needed for health in a certain amount free radicals are damaging and dangerous so that there are no excess free radicals the body needs antioxidants as body protectors, so in this study a total flavonoid level test and antioxidant activity test of ethanol extract and n fraction were carried out. -hexane, ethyl acetate efraction, and water fraction using the FRAP method with the aim of knowing the secondary metabolites contained in the ethanol extract of white pomegranate peel (Punica granatum L.) and determining the total flavonoid content in white pomegranate peel (Puunica granatum L.) and determine the value of antioxidant activity in the ethanol extract of white pomegranate peel (Punica granatum L.) using the FRAP method. The method used in this research is experimental research. The research phase started with sampling, determination of plants, manufacture of simplicia, preparation of extracts, screening of phytochemicals, preparation of test solutions, determination of flavonoid levels, testing of antioxidant activity, and data analysis. Secondary metabolite compounds in the ethanol extract of white pomegranate peel (Punica granatum L.) include alkaloids, flavonoids, tannins, terpenoids and saponins. The total flavonoid content of white pomegranate peel extract (Punica granatum L) as seen using UV-Vis spectrophotometry was 55.3 mg QE/g. Ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction of white pomegranate peel extract (Punica granatum L) had antioxidant activity with values of 2,501 mgQE/g sample, 3,125 mgQE/g sample, 3,055 mgQE/g sample, respectively , 30,516 mgQE/g sample, if you look at using the FRAP method.